3D customized and flexible tactile sensor using a piezoelectric nanofiber mat and sandwich-molded elastomer sheets. (24th March 2017) - Lee, Han Bit; Kim, Young Won; Yoon, Jonghun; Lee, Nak Kyu; Park, Suk-Hee
Abstract: We developed a skin-conformal flexible sensor in which three-dimensional (3D) free-form elastomeric sheets were harmoniously integrated with a piezoelectric nanofiber mat. The elastomeric sheets were produced by polydimethylsiloxane (PDMS) molding via using a 3D printed mold assembly, which was adaptively designed from 3D scanned skin surface geometry. The mold assembly, fabricated using a multi-material 3D printer, was composed of a pair of upper/lower mold parts and an interconnecting hinge, with material properties are characterized by different flexibilities. As a result of appropriate deformabilites of the upper mold part and hinge, the skin-conformal PDMS structures were successfully sandwich molded and demolded with good repeatability. An electrospun poly(vinylidene fluoride trifluoroethylene) nanofiber mat was prepared as the piezoelectric active layer and integrated with the 3D elastomeric parts. We confirmed that the highly responsive sensing performances of the 3D integrated sensor were identical to those of a flat sensor in terms of sensitivity and the linearity of the input–output relationship. The close 3D conformal skin contact of the flexible sensor enabled discernable perception of various scales of physical stimuli, such as tactile force and even minute skin deformation caused by the tester's pulse. Collectively from the 3D scanning design to the practical application, our achievements can potentially meet the needs of tailored human interfaces in the field of wearable devices and human-like robots.